Imo State Agricultural Development Programme Volume 1 Main Report (Owerri Imo State Agricultural Development Programme (ISADP), 1980)
A report containing the findings of an agricultural planning mission which visited Imo State in July 1980. The objective of the mission was to prepare a report for the integrated Agricultural Development Programme (ADP) to be submitted to the World Bank as an application for funding assistance.
lje 04/07/17
Loans
Keywords: Agricultural development -Imo state-Nigeria; Agricultural development